Pengaruh Gaya Kepemimpinan, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan - Muhammad Faizal Rizky; Sugeng Suroso; Ery Teguh Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted with the aim of knowing partially and simultaneously the independent variables, namely Leadership Style, Motivation and Work Discipline, on the dependent variable, namely Employee Performance. This research was conducted at PT. Champ Resto Indonesia Bekasi branch. The data analysis used is the classical analysis test and multiple regression analysis, to test and prove the research hypothesis using the SPSS Version 26 application. Data collection was carried out by distributing questionnaires to 51 employees at PT. Champ Resto Indonesia Bekasi branch. Partially the results show that the Leadership Style variable has a significant effect on Employee Performance, with the results showing t-count (4.017) > t-table (2.012) sig (0.01) < (0.05) the Motivation variable has a significant effect on Performance Employees, with the results showing t-count (3.045) > t-table (2.012) sig (0.03) < (0.05). And the Work Discipline variable has a significant effect on Employee Performance, with t-count results (4.496) > (2.012) sig (0.00) < (0.05). Simultaneously, the results obtained from this research are that the Leadership Style, Motivation and Work Discipline variables simultaneously have a significant effect on the Employee Performance variable with results showing f-count (7.998) > f-table (2.80) sig (0.00) < (0.05). Contribution of Leadership Style, Motivation and Work Discipline to PT Employee Performance. Champ Resto Indonesia Bekasi Branch 68.1%.